Bi2MoO6/Fe-MOF nanocomposites: An efficient adsorbent for chlortetracycline, oxytetracycline, and doxycycline in water - Bai Sun; Yiming Shi; Haiyan Zhou; Chengqi Ye; Yuxian Guo; Yun Wang; Lining Bao; Xiangxiang Wang; Mingjian Yi; Shuguang Zhu (Desalination and Water Treatment)
In this paper, a nanocomposite Bi2MoO6/Fe-MOF (BFeM) with high adsorption capacity was prepared by the solvothermal method. It consists of flake-assembled nanoflowers of Bi2MoO6 and Fe-MOF. As an adsorbent for three tetracycline antibiotics (chlortetracycline (CTC), oxytetracycline (OTC) and doxycycline (DOX)), it has high adsorption capacity. At 323 K, the maximum adsorption capacities of CTC, OTC and DOX were 366.300 mg/g, 374.532 mg/g and 398.406 mg/g, respectively. The comprehensive kinetic study revealed that the adsorption of BFeM on the three antibiotics was primarily chemical adsorption (pseudo second-order kinetics) and intragranular diffusion. The adsorption isotherms showed that the adsorption of BFeM on the three antibiotics followed the Langmuir adsorption isotherm model, indicating mainly monolayer adsorption. Thermodynamic studies showed that the adsorption of the three antibiotics was spontaneous. Under a certain range of pH values, the removal efficiency of the three antibiotics using BFeM as the adsorbent remained at a relatively high level. Furthermore, after five cycles of regeneration experiments, the removal rates of CTC, OTC, and DOX decreased by only 9.21 %, 6.75 %, and 3.69 %, respectively, indicating that the adsorbent exhibits a good regeneration performance. In general, BFeM displays a great potential for removing tetracycline antibiotics from water.